Hirnforschung und Theologie - Evers, Dirk (Theologische Literaturzeitung, 2006)
Recent brain research revealed close Connections between the human brain and human consciousness. This empirical data has been used to argue for a thorough revision of human self-understanding and has caught the attention even of the wider public. The essay deals with these arguments critically. In a first part it gives a brief review over some relevant issues in neuroscience. In a second part it discusses the proclaimed challenges for our human selfunderstanding from a theological perspective. This discussion concentrates on three major issues, namely the question of freedom of will, the quest for the neurophysiological basis of human personality and identity, and the relation between neuroscience and religious experience.